How to establish dialogue between researchers and policymakers for climate change adaptation in Mali: Analysis of challenges, constraints and opportunities - Sogoba, Bougouna; Ba, Allassane; Zougmoré, Robert B.; Samaké, Ouodiouma B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Mali is an agro-forestry-pastoral Sahel country whose economy is based mainly on agriculture, a sector which nevertheless depends on climate variability and change. Indeed, climate change and variability affect agriculture, while agriculture and natural resources management also affect the climate system. In Mali, a country with a semi-arid tropical climate, climate change is an unprecedented threat to the food security of the population, especially people whose livelihoods depend on small-scale agriculture. In order to develop practical solutions for agriculture and food security, we now need to consider, in an innovative and understandable manner, knowledge on climate change, agriculture and food security; we therefore need to include climate issues in national policies and strategies for actions that help to enhance the resilience of rural populations. The exchange of information and knowledge between actors is therefore essential to ensure that decisions on policies, strategies and actions to fight against climate change are based on the best data. This study report, which has been produced as part of activities of the National Science- Policy Dialogue Platform on Climate Change, Agriculture and Food Security in Mali (CCAFS Mali), sheds light, for the various actors, on the current situation of institutions, challenges, constraints and opportunities for operational dialogue between researchers and policymakers for climate change adaptation. Eight key messages have been drawn from the study, and they concern: (1) the current status of the existing institutional system for operational dialogue; (2) the organization and operational difficulties of institutions involved in the fight against climate change; (3) the need for enhanced partnership between the institutions; (4) the need for adequate financial support; (5) the current status of dialogue between researchers and policymakers in Mali; (6) constraints on operational dialogue between researchers and policymakers in Mali; (7) opportunities for operational dialogue between researchers and policymakers in Mali; and (8) the need for a communication forum for researchers and policymakers in Mali. Consideration and analysis of these messages should lead to actionable recommendations to improve interinstitutional dialogue and well-informed decision-making. Any resulting policy decisions could certainly help to promote climate-smart agriculture and improve the resilience of farms in Mali. French version: http://hdl.handle.net/10568/51373